2023
DOI: 10.1038/s41467-023-39778-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of plasmid-borne resistance to sulfonamide antibiotics

Abstract: The sulfonamides (sulfas) are the oldest class of antibacterial drugs and inhibit the bacterial dihydropteroate synthase (DHPS, encoded by folP), through chemical mimicry of its co-substrate p-aminobenzoic acid (pABA). Resistance to sulfa drugs is mediated either by mutations in folP or acquisition of sul genes, which code for sulfa-insensitive, divergent DHPS enzymes. While the molecular basis of resistance through folP mutations is well understood, the mechanisms mediating sul-based resistance have not been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Sulfa drugs work by interacting with the dihydropteroate synthase (DHPS) enzyme and preventing the synthesis of folate, which finally inhibits bacterial cell division. [24] In this study, we showed that the compounds Sul1-5 possess a very important antibacterial activity against Gram negative clinical strains especially against E. coli and K. pneumoniae with very low and interesting MICs values. P. aeruginosa showed a sensibility, only towards tow compounds (Sul1 and Sul4) and S. aureus strains were resistant to these compounds.…”
Section: Discussionmentioning
confidence: 83%
“…Sulfa drugs work by interacting with the dihydropteroate synthase (DHPS) enzyme and preventing the synthesis of folate, which finally inhibits bacterial cell division. [24] In this study, we showed that the compounds Sul1-5 possess a very important antibacterial activity against Gram negative clinical strains especially against E. coli and K. pneumoniae with very low and interesting MICs values. P. aeruginosa showed a sensibility, only towards tow compounds (Sul1 and Sul4) and S. aureus strains were resistant to these compounds.…”
Section: Discussionmentioning
confidence: 83%
“…qnrS1, associated with quinolone resistance, protects DNA gyrase from inhibition by quinolone antibiotics [34]. sul1 and sul2 genes mediate resistance to sulfonamides by encoding di-hydropteroate synthase enzymes [35]. The tetA(B) gene, conferring tetracycline resistance, is associated with efflux pump mechanisms that extrude tetracycline from bacterial cells [36].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in drug resistance has impaired the clinical efficacy of sulfonamides and seriously threatened global public health ( Venkatesan et al, 2023 ). The clinically isolated MDR E. coli is resistant to sulfonamides through gene replacement, that is, obtaining the dihydropteroate synthetase (DHPS) substitutes encoded by the drug resistance genes sul2 and sul3 ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%